Faktor-Faktor yang Mempengaruhi Loyalitas Pelanggan Muslim pada Sa Bakery Ngawi - Sugeng Nugroho Hadi; Salihah Khairawati; Nur Hawa Meizara (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Gaining loyal customers is a blessing for any business, including in the bakery business. The question then arises, "What factors influence customer loyalty?" This study aims to determine the factors influencing customer loyaltyfrom an Muslimc perspectiveat SA Bakery Ngawi. The results of interviews with customers and a recap of previous research revealed 15 indicators influencing customer loyalty. A factor analysis was then conducted using the Dimension Reduction program from SPSS 25. Of the 15 indicators, 11 remained factorable: taste, friendliness, cake design, custom cakes, product quality, product variants, delivery orders, affordable prices, ordering requests, satisfaction, and ease of service. This study was designed using a quantitative descriptive approach. The research sample was the Ngawi community who had made several purchases at SA Bakery. The research data used primary data sourced from a questionnaire with one indicator per questionnaire. The sampling technique used nonprobability quota purposive sampling, with a sample size set at 100 samples. The results showed that in the factor analysis process, one factor was formed, subsequently named "Sharia Product Attributes". Where in these attributes there are two interrelated aspects, namely the aspect of sharia goods in this case, sharia cakes, which are halal and thayyiban, and the aspect of sharia services within the framework of akhlaqul karimah values.